Split payment and criminal fiscal law - Ochman, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The purpose of the article is to present solutions in Polish criminal fiscal law aimed at protecting the mandatory use of the split payment mechanism. The analysis is preceded by a brief overview of instruments aimed at counteracting tax fraud as well as the effects of tax fraud. The main element of the article are considerations regarding article 57c of the Criminal Fiscal Code penalising making payments without using the split payment mechanism.
Keywords: prawo karne skarbowe; przestępstwo skarbowe; oszustwo podatkowe; podział płatności